The relationship between organizational culture and public relations in business organizations - Terek Stojanović, Edit; Vlahović, Marko; Nikolić, Milan; Mitić, Siniša; Jovanović, Zoran (Journal of Business Economics and Management, 2020)
The study presents the results of the impact of organizational culture on public relations in business organizations. The data were obtained from a survey of 415 respondents from 93 companies in Serbia. The following statistical methods were used: descriptive statistics, correlation analysis, regression analysis and hierarchical regression analysis. Some of the most important conclusions of the research follow: In most cases, the organizational culture dimensions have a statistically significant and positive influence on the communication models of public relations (CMPR) dimensions and the organization – public relations (OPR) dimensions; A favorable organizational culture (represented through the favorable values of the organizational culture dimensions) has a positive impact on two-way models of communication, especially the symmetrical model, as well as on most of the OPR dimensions. On the other hand, an unfavorable organizational culture encourages one-way communication and the organization’s orientation solely for its own benefit; The Power Distance dimension acts in contrast to the other dimensions of organizational culture: high power distance impedes two-way communication and promotes the utility of the company, all of which causes public distrust and dissatisfaction.